Waste reduction rate, selected agronomic properties, and effect on bekenu series soil pH buffering capacity of black soldier fly larvae frass - David, Cassandra Sarah; Omar, Latifah; Ahmed, Osumanu Haruna; Mohd Roslim, Muhammad Huzaifah; Krishnan, Kavinraj (Maximum Academic Press, 2024)
Black soldier fly larvae (BSFL) were used in this study as decomposer agents to ingest decanter cake (DC) and palm kernel expeller (PKE) mixture into frass (larvae excretion). The objectives of the study were to: (i) assess the waste reduction rate (WRR) of BSFL frass produced from DC and PKE mixture as feeding substrates using different treatment weights of BSFL, (ii) determine the selected agronomic properties and phytotoxicity effect of the BSFL frass, and (iii) evaluate BSFL frass application effect on the Bekenu Series soil pH buffering capacity. The BSFL rearing was conducted in five treatments using a similar amount of DC and PKE mixture (15 kg) as feeding substrates but under different treatment weights of the BSFL. The WRR averages of all treatments were between 81% to 83% suggesting that the BSFL can degrade most of the feeding substrates (15 kg) regardless of the BSFL weight. The average temperature of feeding substrates throughout BSFL rearing was 27 °C irrespective of the BSFL weight. All of the treatments (T1−T5) produced frass on the 54 d of the BSFL rearing process. The BSFL frass has good agronomic properties reflected by the appropriate value of pH (7.4), and significant amount of total nitrogen (2.5%), organic matter (74%), and some of the beneficial elements (calcium, phosphorus, and magnesium) that could be used as organic fertilizer. No phytotoxicity effect detected in maize seed germination suggested that the BSFL frass is safe to be used as soil organic amendment. Although with neutral pH, the BSFL frass did not affect Bekenu soil pH buffering capacity.